Leading School Turnaround and Improvement in Malaysia and Indonesia / Alma Harris, Michelle Jones, Donnie Adams, Bambang Sumintono and Nashwa Ismail - Harris, A.; Jones, M. S.; Adams, D.; Sumintono, B.; Ismail, N. (The Head Foundation, 2017)
Improving the fortunes of low-performing schools, often in the most challenging circumstances, remains a persistent and pervasive challenge in many education systems (Meyers & Darwin, 2017). This working paper outlines the findings from a small, qualitative comparative research project funded by the HEAD Foundation. The working paper commences with some explanation and contextualization of the idea of ‘turnaround schools’ from the literature. It presents the research methodology and subsequently outlines the main findings from the research project.